Prevalence and risk factors of under-five mortality due to severe acute malnutrition in Africa: a systematic review and meta-analysis - Joshua Wambua; Anahita Ali; Jean Baptiste Ukwizabigira; Paul Kuodi (Systematic Reviews)
Abstract Background Despite a global drop of under-five mortality by 59% between 1990 and 2019, it remains high in Low- and Middle- income Countries (LMICs)with a preponderance in Sub-Saharan Africa (SSA), Southern and Central Asia. Besides preterm and intrapartum complications, undernutrition contributes 45% of the deaths in these developing regions. In Africa, under-five mortality due to severe acute malnutrition (SAM) has stagnated at 10–40%, higher than WHO targets and the SDGs projections. Methods We searched MEDLINE (via PubMed), Scopus, Web of Science, Science direct, Google Scholar, Cochrane Library and Open Grey databases for literature reporting under-five mortality due to SAM in Africa from 2014 to 2024. Estimates of the primary and secondary outcomes were pooled using a random-effects meta-analysis due to the anticipated between study heterogeneity. Results Fifty-two out of 82 studies (63.4%) analyzed reported an overall under-five mortality of 11% (95%CI: 0.08–0.13). Diarrheal diseases, human immunodeficiency virus (HIV) and pneumonia were the three most frequently reported risk factors associated with mortality by 21 (40.1%), 20 (38.5%), and 14 (26.9%) studies, respectively. No significant regional variation was found. Conclusion Under-five mortality due to SAM in Africa is still high as reported in the included studies. There were no regional variations. Diarrheal diseases, HIV and pneumonia were the most frequently reported risk factors associated with under-five mortality due to SAM in Africa.